2020
DOI: 10.1002/pbc.28533
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and feasibility of a parent‐targeted dietary intervention in young survivors of childhood cancer: “Reboot”

Abstract: Background Assess the acceptability and feasibility of delivering Reboot, a telephone dietary intervention to parents of pediatric cancer survivors. The research question asks whether tailored dietary support is acceptable and feasible to deliver to parents of young cancer survivors who have recently completed cancer treatment? Procedure Pre‐post study. Nineteen parents of pediatric cancer survivors (aged 2‐13 years) in remission, who had received cancer treatment at a tertiary children's hospital, less than 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…This trifecta of treatment side effects, negative feeding practices and poor messaging from health professionals creates a challenging environment to optimise nutrition. While interventions exist to address unhealthy behaviours among survivors and can include strategies to address negative feeding practices, 29,35,36 no studies have examined the nutrition messages provided by health professionals within the multidisciplinary team.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This trifecta of treatment side effects, negative feeding practices and poor messaging from health professionals creates a challenging environment to optimise nutrition. While interventions exist to address unhealthy behaviours among survivors and can include strategies to address negative feeding practices, 29,35,36 no studies have examined the nutrition messages provided by health professionals within the multidisciplinary team.…”
Section: Discussionmentioning
confidence: 99%
“…An existing program that focuses on behaviour change strategies to restore healthy eating practices in survivors using an online, parent-led intervention is Reboot-Kids ® , 40 which has demonstrated an increase in parent confidence in providing more nutritious foods to survivors. 36 Using an online platform aligns with the desire for participant autonomy in intervention timing. Contact with a dietitian/feeding therapist may be more appropriate for concerns such as food aversions, sudden weight changes, or nasogastric tube weaning.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several approaches are being implemented targeting the family-based nutrition and cooking education of parents and guardians of children with cancer [ 71 , 72 , 73 ]. Among such interventions, web-based dietary and cooking intervention approaches have gained great attention among parents and young patients [ 74 , 75 , 76 ]. Preliminary results have shown that early interventions resulted in better nutrition practices, i.e., lower sodium consumption [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing educationbased interventions promoting healthy lifestyles among CCS have been effective [26,31], and similar to previous research [34,35], the interviews in the present study highlighted the importance of family involvement. An existing programme that focuses on behaviour change strategies to restore healthy eating practices using an online, parent-led intervention is Reboot-Kids ® [36], which has demonstrated an increase in parent con dence in providing more nutritious foods to CCS [32]. Using an online platform aligns with the desire for participant autonomy in intervention timing.…”
Section: Discussionmentioning
confidence: 99%
“…This trifecta of treatment side effects, negative feeding practices, and poor messaging from health professionals creates a challenging environment to optimise nutrition. While interventions exist to address unhealthy behaviours amongst CCS and can include strategies to address negative feeding practices [26,31,32], no studies have examined the nutrition messages provided by health professionals within the MDT.…”
Section: Discussionmentioning
confidence: 99%